Adverse Events in Laparoscopic Appendectomy Under Spinal Anesthesia: Intraoperative and Postoperative Perspectives - Mahmud, Ashik; Nahar, Nishat Un; Masum, Mohammad Golam; Adel, Ashraf Siddik; Bhuiyan, N I; Roy, Proshanta (Journal of Brahmanbaria Medical College, 2026)
Background: Laparoscopic Appendectomy (LA) has become the preferred approach for treating acute appendicitis due to its minimally invasive nature, which leads to reduced postoperative discomfort, shorter hospital stays, and faster recovery compared to open appendectomy. This study evaluates the efficacy and safety of LA performed under spinal anesthesia in a resource-limited setting, aiming to provide insights into patient outcomes and adverse effects. Materials and methods: This prospective observational study was conducted at Brahman Baria Medical College Hospital over a 28-month period from February 2022 to June 2024, the study included 188 patients (108 females, 80 males, mean age 25.5 years) diagnosed with acute appendicitis. Patients were selected based on specific inclusion criteria and underwent routine blood tests and ultrasound examinations. Results: The results indicated a mean surgery time of 22.80 minutes and a mean hospital stay of 2 days. Intraoperative complications were minimal, with shoulder pain and nausea being the most common. Postoperative adverse events included nausea, vomiting, and mild shoulder pain, showcasing that while complications were present, they were generally mild and manageable. Conclusion: The study highlights the effectiveness and safety of LA in a limited-resource environment, contrasting outcomes with those in higher-income countries, emphasizing the importance of healthcare infrastructure and technology in surgical outcomes. Journal of Brahmanbaria Medical College Volume 07 Issue 01 January 2025 ; 11-15